Toyota under fire [ lessons for turning crisis into opportunity - Liker, Jeffrey K.; Ogden, Timothy N. (McGraw-Hill, 2011)
The first comprehensive look at the 2009-2010 Toyota recall: A case study of how to overcome a major management crisis--from Jeffrey Liker, author of the bestselling The Toyota Way